2008
DOI: 10.1007/s10597-008-9128-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Early Attrition from Psychosocial Rehabilitation Programs

Abstract: This study aimed to identify characteristics associated with early dropout from a vocationally oriented psychosocial rehabilitation (PSR) program for clients with severe mental illness. The sample consisted of 194 individuals who participated in a study comparing a supported employment program to a stepwise vocational program. Study participants who dropped out of the PSR program within 6 months of study entry were compared to those who continued for at least 6 months. Dropouts had poorer competitive employmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Clients with less than a high school degree were less likely to find employment (Burke-Miller et al 2006) as was the case with low-skilled clients (Van Erp et al 2007). Clients with at least a high school degree were not only more likely to obtain work, they were also more likely to stay within the SE program and in treatment (Cook 2007;Harding et al 2008). Accordingly, some researchers suggest that vocational rehabilitation should support clients' completion of secondary and post-secondary education (Burke-Miller et al 2006).…”
Section: Intrinsic Characteristicsmentioning
confidence: 99%
“…Clients with less than a high school degree were less likely to find employment (Burke-Miller et al 2006) as was the case with low-skilled clients (Van Erp et al 2007). Clients with at least a high school degree were not only more likely to obtain work, they were also more likely to stay within the SE program and in treatment (Cook 2007;Harding et al 2008). Accordingly, some researchers suggest that vocational rehabilitation should support clients' completion of secondary and post-secondary education (Burke-Miller et al 2006).…”
Section: Intrinsic Characteristicsmentioning
confidence: 99%
“…These findings are important as studies that have followed drop-outs from PSR programs have typically shown poorer employment and rehospitalization outcomes (Harding et al 2008; Beard et al 1978; Bond 1992; Cook and Razzano 1995) for these clients. These findings emphasize the importance of identifying factors that may be associated with early drop-out, to help develop methods for enhancing participation in PSR activities.…”
Section: Introductionmentioning
confidence: 95%
“…Despite these findings, high-rates of early drop-out from PSR community day programs that treat clients with severe mental illness and include interventions recommended by PORT are common, with rates ranging from mid-20% (e.g., Harding et al 2008) to nearly 50% (e.g., Cohen et al 1995) in some studies, with differences most likely linked to sample diagnoses, definitions for attrition and other individual and program factors. These findings are important as studies that have followed drop-outs from PSR programs have typically shown poorer employment and rehospitalization outcomes (Harding et al 2008; Beard et al 1978; Bond 1992; Cook and Razzano 1995) for these clients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairment is a central feature of schizophrenia, affects everyday functioning, and limits benefit from psychiatric rehabilitation (Green, 1996; Harding et al, 2008; McGurk et al, 2004; Velligan et al, 1997; Walsh et al, 2003). Cognitive training or remediation is an intervention to improve cognition in this population; the most recent meta-analysis of 2,104 participants demonstrated effect sizes of 0.45 on cognition and 0.42 on functioning, with no evidence that treatment approach or duration affected cognitive outcome (Wykes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%